1991
DOI: 10.1097/00004032-199112000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Home 222Rn and Gamma-ray Exposure Measured in 52 Dwellings

Abstract: A personal 222Rn and gamma-ray detector has been developed. The detector precision is limited only by the Poisson counting error and has a lower limit of detection in this study of 4.5 kBq m-3 h (4 pCi L-1 day). The detector was used in a study of 52 homes in Illinois to measure the personal exposure vs. the simultaneous exposure on all levels of the home. The ratio of personal exposure to basement 222Rn concentration averaged 0.22, with a high degree of scatter (R2 = 31%). The ratio of personal exposure to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, the New Jersey Radon/ Lung Cancer Study (Schoenberg et al 1990) reported summary data that revealed very little difference in radon concentrations between the floors. In contrast, a study of 52 homes in Illinois found a 0.20 ratio between first floor and basement radon concentrations (Harley et al 1991). The New Jersey (Schoenberg et al 1990) and Illinois (Harley et al 1991) findings suggest that IRLCS data may not be representative of other areas of the United States that have a different climate, geologic characteristics, and housing stock.…”
Section: Resultsmentioning
confidence: 97%
“…However, the New Jersey Radon/ Lung Cancer Study (Schoenberg et al 1990) reported summary data that revealed very little difference in radon concentrations between the floors. In contrast, a study of 52 homes in Illinois found a 0.20 ratio between first floor and basement radon concentrations (Harley et al 1991). The New Jersey (Schoenberg et al 1990) and Illinois (Harley et al 1991) findings suggest that IRLCS data may not be representative of other areas of the United States that have a different climate, geologic characteristics, and housing stock.…”
Section: Resultsmentioning
confidence: 97%
“…Associations observed at the aggregate level (postcode sector) may not necessarily hold at the level of the individual. 39 A final point regarding exposure estimation is that exposure and outcome measures are for the same point in time, and we therefore assume current exposure (based on long-term accumulated radon measurements for current residence location) is a reasonable estimate of total exposure. Further, as indicated elsewhere, it is possible that the observed association is due to unmeasured or residual confounding.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…(9) if , f 3 >> a,, aiid to Eq. (10) if C, is time independent, which is ident.ica1 t o Cohcn's expression (15). Thc other bounclary condition relates to the radon concentration at the bottom of the charcoal bed.…”
Section: Y(l T) = Kpcs ( 5 )mentioning
confidence: 96%